2019
DOI: 10.1177/1479973118820310
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of early rehabilitation on patients with chronic obstructive lung disease and acute respiratory failure in intensive care units: A case–control study

Abstract: The effect of early rehabilitation on the outcome of patients with chronic obstructive pulmonary disease (COPD) and acute respiratory failure (ARF) in intensive care units (ICUs) remains unclear. We examined the effect of early rehabilitation on the outcomes of COPD patients requiring mechanical ventilation (MV) in the ICU. This retrospective, observational, case–control study was conducted in a medical center with a 19-bed ICU. The records of all 105 ICU patients with COPD and ARF who required MV from January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Another important finding was that the earlier PR was introduced post-ICU and the longer the duration of PR, the better patients recovered their physical capacity. This observation corroborates previous results in COPD and respiratory failure patients emphasizing the need for early PR following ICU ( Chou et al, 2019 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Another important finding was that the earlier PR was introduced post-ICU and the longer the duration of PR, the better patients recovered their physical capacity. This observation corroborates previous results in COPD and respiratory failure patients emphasizing the need for early PR following ICU ( Chou et al, 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…Critically ill patients exhibiting respiratory failure were admitted to the intensive care unit (ICU) for prolonged stays, subsequently requiring a rehabilitation program to deal with the consequences of artificial ventilation and prolonged inactivity ( Polastri et al, 2020 ; Vitacca et al, 2020 ; Thomas et al, 2020 ). Pulmonary rehabilitation (PR) has proven to be effective in respiratory patients following mechanical ventilation ( Chou et al, 2019 ) and in patients with the most common pulmonary disease, chronic obstructive pulmonary disease, at all stages and recovering from acute exacerbations ( Puhan et al, 2005 ). Although PR has been suggested following severe COVID-19 ( Spruit et al, 2020 ), there is still a lack of data demonstrating its effectiveness on recovery of physical and psychosocial parameters in severe COVID-19 patients following an ICU stay.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have shown [6] that some patients have varying degrees of psychological negativity in the early stages of treatment, which affects the effect of ventilation and increases the risk of poor prognosis, so appropriate nursing interventions need to be given to patients during treatment to improve the prognosis. Most of the conventional nursing tools currently used in the clinic are based on the patient's condition in order to maintain treatment, ignoring to some extent the differences in patients' stage needs [7][8][9]. Stage-based nursing measures are the hotspot studied at present, which was reported [10] that such nursing means can implement targeted measures and interventions at different stages.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, no clinical study has evaluated early rehabilitation effects on COVID-19 patients to date. However, an earlier rehabilitation program for acute respiratory failure in the ICU setting has been proven to increase survival rate, increase successful extubation rate, reduce mechanical ventilation (MV) duration, reduce ICU and hospital stays, and lower medical costs [ 13 ].…”
Section: Discussionmentioning
confidence: 99%